Improving Eye Contact and Gaze Following in Children with Autism Spectrum Disorder: Systematic Withdrawal of Stimulus Prompts and Tangible Reinforcers. Issue 6 (November 2022) - Lee, Gabrielle T.; Tang, Yuwei; Xu, Sheng
The purpose of this study was to investigate the effects of a procedure involving systematic withdrawal of stimulus prompts and tangible reinforcers on the acquisition, maintenance, and generalization of eye contact and gaze following for two children with ASD in China. Two boys with ASD (5–6 years of age) participated. A concurrent multiple probe design across behaviors and participants was used. Results indicate that the procedure effectively established eye contact and gaze following for both children. Generalization to new instructors occurred in the free play setting, and the acquired behaviors were maintained for 1 month following training. Eye contact was maintained with social consequences for one child; the other child required tokens along with social consequences to maintain eye contact. Social consequences were sufficient to maintain gaze following for both children.